2020
DOI: 10.2516/ogst/2020063
|View full text |Cite
|
Sign up to set email alerts
|

A review on polymer, gas, surfactant and nanoparticle adsorption modeling in porous media

Abstract: Adsorption is a rock surface phenomenon and has increasingly become popular, especially in particle-transport applications across many fields. This has drawn a remarkable number of publications from the industry and academia in the last decade, with many review articles focused on adsorption of polymers, surfactants, gas, and nanoparticles in porous media with main applications in Enhanced Oil Recovery (EOR). The discussions involved both experimental and modeling approaches to understanding and efficiently mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 135 publications
(177 reference statements)
0
12
0
Order By: Relevance
“…Previous work has indicated that the gas flow performance in tiny shale pores is mainly slip and viscous flow in larger nanopores but Knudsen diffusion and surface diffusion in smaller nanopores . The imbalance of attractive forces between fluid molecules and a material surface leads to the accumulation of the adsorbate molecules on the surface of the adsorbent; this process is known as adsorption . The contribution of adsorbed gas mainly includes two aspects.…”
Section: Multiscale Flow Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has indicated that the gas flow performance in tiny shale pores is mainly slip and viscous flow in larger nanopores but Knudsen diffusion and surface diffusion in smaller nanopores . The imbalance of attractive forces between fluid molecules and a material surface leads to the accumulation of the adsorbate molecules on the surface of the adsorbent; this process is known as adsorption . The contribution of adsorbed gas mainly includes two aspects.…”
Section: Multiscale Flow Simulationmentioning
confidence: 99%
“…111 The imbalance of attractive forces between fluid molecules and a material surface leads to the accumulation of the adsorbate molecules on the surface of the adsorbent; this process is known as adsorption. 112 The contribution of adsorbed gas mainly includes two aspects. First, the adsorbed gas reduces the pore cross-section, which leads to an increment in the slippage effect.…”
Section: Diffusion and Flowmentioning
confidence: 99%
“…First, the electrostatic repulsion induced by nanoparticles decreases the bridging polarity head of the surfactants, effectively reducing their adsorption on rock surfaces. , This allows surfactants to penetrate deeper into the formation and maintain interaction with oil for extended periods. Second, the irreversible adsorption of nanoparticles on emulsion droplet surfaces in nanoemulsions strengthens their formation and stability.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Consequently, competitive deposition between GO and bio-surfactant for the surface effective sites played an important role in the enhanced transport of GO by saponin. [70][71][72] That is, the adsorbed saponin molecules masked the heterogeneity of the porous media surface. 73,74 Third, in Fig.…”
Section: Papermentioning
confidence: 99%
“…As mentioned earlier, the primary mechanisms of the promotion effect of saponin on GO transport stemmed from the increased electrostatic repulsion, the steric hindrance, and the decreased straining effect, as well as the competition between nanoparticles and saponin molecules for effective attachment sites. 25,66,70,72,73,75 Notably, unlike Na + , as a transition metal ion, Cu 2+ ions have a great capacity for complexing with carbon-based compounds containing functional groups. 85 It is well known that silicon dioxide and iron oxide contain a large number of surface hydroxyl groups (i.e., ^Si-OH and ^Fe-OH).…”
Section: Effects Of Saponin On Go Mobility In the Presence Of Divalen...mentioning
confidence: 99%